The Pengaruh Social Media Marketing Melalui Instagram Terhadap Purchase Intention yang Dimediasi Brand Awareness di Interkultural Edukasi Partner - Mikhael Mikhael; Marcellia Susan (Forum Kerjasama Pendidikan Tinggi (FKPT), 2022)
The potential for consumer interaction and the intensity of the use of social media is a promising opportunity for companies to carry out social media marketing. In other words, companies that do not use social media marketing will lose the opportunity to reach their consumers so that consumers will not recognize the product. In turn, it will have an impact on the decline in the purchase intention of these consumers. The purpose of this study was to determine the effect of social media marketing, brand awareness, and purchase intention. The sample was 127 respondents from Bandung who had accessed the Interkultural Edukasi Partner's Instagram account in the past year but had never been registered as a student. The data is processed using a variance-based structural equation model (SEM) with partial least squares (PLS). The results show that there is no direct influence of social media marketing on purchase intention, there is an influence of social media marketing on brand awareness, there is an influence of brand awareness on purchase intention, and there is an influence of social media marketing on purchase intention through brand awareness.